Sclerotherapy of Vascular Malformations in the Oral Cavity—Minimizing Postoperative Morbidity - Itai Zeevi; Gavriel Chaushu; Michael Alterman; Liat Chaushu (Medicina, 2020)
Vascular malformations (VMs) are a wide vascular or lymphatic group of lesions common on the head and neck. The objective of this study was to assess the efficacy and morbidity of sclerotherapy for the treatment of VMs in the oral and perioral area. Special attention was given to factors that may contribute to minimizing postoperative morbidity. Data from 25 patients (32 lesions) with oral VMs submitted to sclerotherapy with monoethanolamine oleate (EAO) were included. A structured form was used to collect data. An arbitrary score was determined to evaluate postoperative morbidity. Each of the following signs or symptoms received one point: pain, swelling, hematoma, ulceration, erythema, transient numbness, and transient itching. Pain and swelling were further divided into mild to moderate (1 point) and severe (2 points). Theoretically, the score was in the range of 0–9. Calculated scores ranged 0–4. The patients were further divided into two groups with scores of 0–1 denoting minimal morbidity (MIN) and 2–4 denoting significant morbidity (SIG). The number of lesions in each morbidity-score group were comparable (MIN 17and SIG 15). There were no statistically significant differences between the groups regarding age, number of applications, or average injection volume per mm lesion. Statistically significant differences were noted regarding gender (p = 0.05), lesion diameter (p = 0.030), total volume of first (p = 0.007) and second application (p = 0.05), and total injected volume (p = 0.03). Factors contributing to the risk for significant morbidity included being male, lesion diameter > 5 mm, volume > 0.3 mL per application, and total injected volume > 0.3 mL. A waiting time of 12 weeks prior to additional EAO application was required in 12 out of 29 lesions for clinical observation of complete regression. It was concluded that sclerotherapy with EAO as monotherapy is easy to apply, safe, and effective within a small number of sessions. Application of <0.3 mL EAO per session, and a waiting time of 12 weeks prior to the second application, would significantly minimize morbidity.